5
$\begingroup$

Could someone help me with this question? I am stuck on it.

Compute the following double integral: $$\int_{y=0}^1\int_{x=y}^1 e^{\large x^2}\ dx\ dy.$$

How to compute the integral when the inner integral is a form of error function? Thanks in advance for your help.

$\endgroup$
8
$\begingroup$

The region of integration $y<x<1$ and $0<y<1$ is corresponding to $0<y<x$ and $0<x<1$, therefore $$ \int_{y=0}^1\int_{x=y}^1\ e^{\large x^2}\ dx\ dy=\int_{x=0}^1\int_{y=0}^x\ e^{\large x^2}\ dy\ dx=\int_{x=0}^1\ e^{\large x^2}\ dx\ \int_{y=0}^x\ \ dy. $$ The last integral is easy to be dealth with and the answer is $\color{blue}{\dfrac12(e-1)}$.

$\endgroup$
  • $\begingroup$ Thank you very much for your answer. One more question, is it possible to compute the inner integral without changing the limit of integral? $\endgroup$ – user151804 May 18 '14 at 15:19
  • 1
    $\begingroup$ @user151804 Please take a look my another answer. Anyway, I really enjoy your problem specially for obtaining the another answer. :) $\endgroup$ – Tunk-Fey May 18 '14 at 16:18
7
$\begingroup$

Another hard way (As the OP's wish):

Using Maclaurin series of exponential function, we will obtain $$ e^{\large x^2}=\sum_{n=0}^\infty\frac{x^{\large 2n}}{n!}. $$ Hence $$ \begin{align} \int_{x=y}^1\ e^{\large x^2}\ dx&=\int_{x=y}^1\ \sum_{n=0}^\infty\frac{x^{\large 2n}}{n!}\ dx\\ &=\sum_{n=0}^\infty\int_{x=y}^1\ \frac{x^{\large 2n}}{n!}\ dx\\ &=\left.\sum_{n=0}^\infty\frac{x^{\large 2n+1}}{(2n+1)\ n!}\right|_{x=y}^1\\ &=\sum_{n=0}^\infty\frac{1-y^{\large 2n+1}}{(2n+1)\ n!} \end{align} $$ and $$ \begin{align} \require{cancel} \int_{y=0}^1\ \sum_{n=0}^\infty\frac{1-y^{\large 2n+1}}{(2n+1)\ n!}\ dy&=\sum_{n=0}^\infty\int_{y=0}^1\ \frac{1-y^{\large 2n+1}}{(2n+1)\ n!}\ dy\\ &=\sum_{n=0}^\infty\left.\left(\frac{y}{(2n+1)\ n!}-\frac{y^{\large 2n+2}}{(2n+2)(2n+1)\ n!}\right)\right|_{y=0}^1\\ &=\sum_{n=0}^\infty\left(\frac{1}{(2n+1)\ n!}-\frac{1}{(2n+2)(2n+1)\ n!}\right)\\ &=\sum_{n=0}^\infty\frac{(2n+2)-1}{(2n+2)(2n+1)\ n!}\\ &=\sum_{n=0}^\infty\frac{\cancel{2n+1}}{2(n+1)\cancel{(2n+1)}\ n!}\\ &=\frac12\sum_{n=0}^\infty\frac{1}{(n+1)!}\\ &=\large\color{blue}{\frac12(e-1)}. \end{align} $$

$\endgroup$
  • $\begingroup$ @user151804 You're welcome. :) $\endgroup$ – Tunk-Fey May 18 '14 at 16:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.